Expanded population of low-density neutrophils in juvenile idiopathic arthritis - Parackova, Zuzana; Zentsova, Irena; Bloomfield, Marketa; Klocperk, Adam; Horvath, Rudolf; Malcova, Hana; Cebecauerova, Dita; Sediva, Anna (Frontiers in Immunology, 2023)
Introduction: Juvenile idiopathic arthritis (JIA), a clinically variable disease characterized by autoimmune arthritis, affects children, and its immunopathology remains elusive. Alterations in neutrophil biology play an important role in this disease. In the present study, we aimed to explore the features of low-density neutrophils (LDNs) in patients with JIA.Methods: Gene expression of peripheral blood mononuclear cells (PBMCs) from children with distinct subtypes of JIA was analyzed by NanoString Immunology panel. Presence of LDNs was ascertained by flow cytometry and the release of neutrophil-associated products were analyzed by LUMINEX.Results: LDNs were detected in patients' peripheral blood mononuclear cells (PBMCs) after density gradient centrifugation. Transcriptomic analysis of JIA PBMCs revealed that genes related to neutrophil degranulation were markedly upregulated. The number of LDNs and level of their degranulation products increased in patients' PBMCs and correlated with serum calprotectin, but not with disease activity, sedimentation rate and C-reactive protein (CRP) levels. The phenotypes of LDNs varied from those of normal-density neutrophils and healthy donor LDNs. Phenotypical analysis revealed LDNs are immature and primed population with decreased suppressive capacity. A negative correlation between surface proteins CD62L, CD66b, and CD11b and the number of inflamed joints/JADAS was established.Our results describe LDNs as primed, degranulated, immature cells with impaired suppressive activities. This work thus contributes to the increasing body of evidence that LDNs in JIA are altered and their role in the disease immunopathogenesis and possible clinical associations should be investigated further.